Polymer-embedded stannic oxide nanoparticles as humidity sensors - Hatamie, Shadie; Dhas, Vivek V.; Kale, B. B.; Mulla, Imtiaz S.; Kale, Sangeeta N. (Materials Science & Engineering C-Biomimetic and Supramolecular Systems, 2009)
Stannic oxide (SnO(2)) nanoparticles have been suspended in polyvinyl alcohol (PVA) matrix in different PVA: SnO(2) molar ratios ranging from 1:1 to 1:5 using simple chemical route. This suspension was deposited on ceramic substrate and upon drying was carefully detached from the substrate. SnO(2)-embedded self-standing, transparent and flexible thin films were hence synthesized. Transmission electron microscopy (TEM) and Xray diffraction (XRD) techniques show the rutile tetragonal structure of SnO(2) with particle size similar to 5 nm. UV-Visible spectroscopy demonstrates the band gap of 3.9 eV, which does not alter when embedded in polymer. Fourier transform infrared spectroscopy (FTIR) reveals that the properties of SnO(2) do not modify due to incorporation in the PVA matrix. The structures work as excellent humidity sensors at room temperature. For a critical PVA:SnO(2) molar ratio of 1:3, the resistance changes to five times of magnitude in 92% humidity within fraction of second when compared with resistance at 11% humidity. The sample regains its original resistance almost instantaneously after being removed from humid chamber. Nanodimensions of SnO(2) particles and percolation mechanism related to transport through polymer matrix and water molecule as a carrier has been used to understand the mechanism. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: humidity sensor; Nanoparticles; Polymer; Stannic oxide

Cobalt nanoparticles doped emaraldine salt of polyaniline: a promising room temperature magnetic semiconductor - Hatamie, Shadie; Kulkarni, M. V.; Kulkarni, S. D.; Ningthoujam, R. S.; Vatsa, R. K.; Kale, Sangeeta N. (Journal of Magnetism and Magnetic Materials, 2010)
Incorporation of magnetic nanoparticles in polymers with organic functional groups working as semiconducting substrate is of immense interest in the field of dilute magnetic semiconductors (DMS) and spintronics. In this article we report on synthesis and evaluation of dilutely doped (0-10 wt%) cobalt nanoparticles in emaraldine salt (ES) of polyaniline in the presence of dodecyl benzene sulfonic acid (DBSA) and p-toluene sulfonic acid (p-TSA) using a sonochemical-assisted-reduction approach as a possible DMS candidate. The X-ray diffraction pattern and high resolution transmission electron microscopy (HRTEM) image show the ES to be polycrystalline, in which 10 nm sized Co nanoparticles get embedded in its FCC structural form. From Fourier transform infrared (FT-IR) and UV-visible (UV-vis) spectroscopy studies, it is predicted that cobalt particles get electrostatically bound to the specific SO(3)(-) ion sites of ES, thereby modifying torsional degrees of freedom of the system. The applied field dependent magnetization study shows that the sample exhibits hysteresis loop with a minimal doping of 3 wt% of Co nanoparticles and increases with the amount of Co nanoparticles in ES due to dipolar interaction. The electron transport data show that with increase in Co wt% there is a gradual shift from ohmic to non-ohmic response to the sample bias, accompanied by opening of electrical hysteresis and an increased resistance. The non-linear response of higher doped systems has been attributed to the combination of direct and Fowler-Nordheim tunneling phenomena in these systems. Persistence of optical and transport properties of the polymer, with an introduction of magnetic moment in the system, envisages the system to be a fine magnetic semiconductor. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Cobalt nanoparticles; Magnetic semiconductor; polyaniline